Patient-level and system-level determinants of stroke fatality across 16 large hospitals in Ghana and Nigeria: a prospective cohort study. Issue 4 (April 2023) - Sarfo, Fred S; Akpa, Onoja M; Ovbiagele, Bruce; Akpalu, Albert; Wahab, Kolawole; Obiako, Reginald; Komolafe, Morenikeji; Owolabi, Lukman; Ogbole, Godwin; Fakunle, Adekunle; Okekunle, Akinkunmi Paul; Asowata, Osahon J; et al.
Summary: Background: Every minute, six indigenous Africans develop new strokes. Patient-level and system-level contributors to early stroke fatality in this region are yet to be delineated. We aimed to identify and quantify the contributions of patient-level and system-level determinants of inpatient stroke fatality across 16 hospitals in Ghana and Nigeria. Methods: The Stroke Investigative Research and Educational Network (SIREN) is a multicentre study involving 16 sites in Ghana and Nigeria. Cases include adults (aged ≥18 years) with clinical and radiological evidence of an acute stroke. Data on stroke services and resources available at each study site were collected and analysed as system-level factors. A host of demographic and clinical variables of cases were analysed as patient-level factors. A mixed effect log-binomial model including both patient-level and system-level covariates was fitted. Results are presented as adjusted risk ratios (aRRs) with respective 95% CIs. Findings: Overall, 814 (21·8%) of the 3739 patients admitted with stroke died as inpatients: 476 (18·1%) of 2635 with ischaemic stroke and 338 (30·6%) of 1104 with intracerebral haemorrhage. The variability in the odds of stroke fatality that could be attributed to the system-level factors across study sites assessed using model intracluster correlation coefficient was substantial at 7·3% (above a 5% threshold). Stroke units were available at only five of 16 centres. The aRRs of six patient-level factors associated with stroke fatality were: low vegetable consumption, 1·19 (95% CI 1·07–1·33); systolic blood pressure, 1·02 (1·01–1·04) for each 10 mm Hg rise; stroke lesion volume more than 30 cm 3, 1·48 (1·22–1·79); National Institutes of Health Stroke Scale (NIHSS) score, 1·20 (1·13–1·26) for each 5-unit rise; elevated intracranial pressure, 1·75 (1·31–2·33); and aspiration pneumonia, 1·79 (1·16–2·77). Interpretation: Studies are needed to assess the efficacy of interventions targeting patient-level factors such as aspiration pneumonia in reducing acute stroke fatality in this region. Policy directives to improve stroke unit access are warranted. Funding: US National Institutes of Health. Translations: For the Twi, Yoruba and Hausa translations of the abstract see Supplementary Materials section.